2021
DOI: 10.1002/2211-5463.13298
|View full text |Cite
|
Sign up to set email alerts
|

Reduced MAGI3 level by HPV18E6 contributes to Wnt/β‐catenin signaling activation and cervical cancer progression

Abstract: Human papillomavirus type 18 (HPV18) has high carcinogenic power in invasive cervical cancer (ICC) development. However, the underlying mechanism remains elusive. The carcinogenic properties of HPV18 require the PDZ-binding motif of its E6 oncoprotein (HPV18 E6) to degrade its target PSD95/Dlg/ZO-1 (PDZ) proteins. In this study, we demonstrated that the PDZ protein membrane-associated guanylate kinase, WW and PDZ domain containing 3 (MAGI3) inhibited the Wnt/b-catenin pathway, and subsequently cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Based on colposcopy and pathology studies, we found consistent results, with nearly half (48.7%) of participants with cervical lesions (CIN 1+) and 11.6% with CIN 2+ lesions requiring further treatment, such as cervical conization [ 68 ]. From the literature, it is suggested that cervical HPV 16 and HPV 18 are associated with 70% of all cases of invasive cervical cancer, and HPV 16 is the most common high-risk subtype, causing over half of all cervical cancer cases [ 69 , 70 ]. Our results showed that cervical HPV 16/18 detection was still not sufficient for predicting CIN 2+ lesions, with 1/3 CIN 2+ patients not covered.…”
Section: Discussionmentioning
confidence: 99%
“…Based on colposcopy and pathology studies, we found consistent results, with nearly half (48.7%) of participants with cervical lesions (CIN 1+) and 11.6% with CIN 2+ lesions requiring further treatment, such as cervical conization [ 68 ]. From the literature, it is suggested that cervical HPV 16 and HPV 18 are associated with 70% of all cases of invasive cervical cancer, and HPV 16 is the most common high-risk subtype, causing over half of all cervical cancer cases [ 69 , 70 ]. Our results showed that cervical HPV 16/18 detection was still not sufficient for predicting CIN 2+ lesions, with 1/3 CIN 2+ patients not covered.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Wnt pathway increases cytoplasmic β‐catenin, subsequently fueling the activation of cyclin genes, culminating in cellular division, growth, and uncontrolled proliferation. HPV18 E6 diminishes MAGI3 levels, contributing to Wnt /β‐catenin signaling activation 125 . E6 proteins from HR‐HPV and LR‐HPV activate the Wnt/ β‐catenin pathway by degrading NHERF1 through E6AP 126 .…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…HPV18 E6 diminishes MAGI3 levels, contributing to Wnt /β‐catenin signaling activation. 125 E6 proteins from HR‐HPV and LR‐HPV activate the Wnt/ β‐catenin pathway by degrading NHERF1 through E6AP. 126 Besides, HPV‐18 E6 oncoprotein and its spliced isoform E6*I regulate the Wnt/β‐catenin cell signaling pathway through upregulating TCF‐4 transcriptional factors.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…[ 9 , 10 ] HPV16 and HPV18 are associated with 70% of all cases of invasive CC, and HPV16 is the most common high-risk subtype, causing over half of all CC cases. [ 11 , 12 ] In 2012, the American Society for Colposcopy and Cervical Lesions and the American College of Obstetricians and Gynecologists issued guidelines clearly stating that people infected with HPV16 and HPV18 should undergo colposcopy even if cytology is negative. [ 13 ] However, fewer than 10% of patients with high-risk HPV subtypes have an infection lasting more than 2 years.…”
Section: Introductionmentioning
confidence: 99%